Perancangan Standard Operating Procedure (SOP) Penatausahaan Pengadaan dan Persediaan Bahan Pangan: Studi Kasus Dapur BGN Cempaka Putih Timur 02 - Shifa Aprilia; Tri Hesti Utaminingtyas; Ellis Annisa (LPPM Universitas Negeri Jakarta, 2026)
The BGN Kitchen at SPPG Cempaka Putih Timur 02 serves about 2,316 to 2,325 beneficiaries daily but, since starting operations in October 2025, has relied on general national guidelines rather than a unit-specific written Standard Operating Procedure (SOP) for procurement and inventory administration. This study designs a procurement and inventory SOP suited to the unit’s operational needs, using a qualitative approach adapted from Sugiyono’s Research and Development method: needs analysis, SOP design, and validation. Data were collected via observation and interviews with five key informants, then analyzed using open and axial coding. The study produced an SOP comprising four flowcharts — purchase authorization, receiving and inspection, inventory management, and stock opname/payment authorization/reporting — addressing gaps such as overlapping Accountant duties, inconsistent stock-opname responsibility, and missing standardized documents. Additional outputs include vendor evaluation forms, standardized transfer descriptions, contract retention, and digitalized stock cards, strengthening segregation of duties and accountability, consistent with Stewardship Theory.